Pengaruh Income Smoothing, Firm Size, Dan Financial Leverage, Terhadap Company Performance - Jihan Nurul Rachman; Nor Norisanti; Acep Samsudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Before making a decision, investors will analyze the company's performance first, one of the ratios used by investors to measure the level of success of a company's performance in assessing shares, the difficulty of investors regarding the valuation of undervalued shares, requires investors to analyze fundamentally, one of which is price to book value. PBV) which shows stock prices are categorized as expensive and cheap in buying and selling shares, investors will definitely choose cheap stocks to maximize profits (return), so the authors are interested in conducting a more in-depth empirical study of the company's performance through proxied stock valuation. with PBV and the factors that influence it. The purpose of this study was to determine the effect of income smoothing, firm size and financial leverage on company performance in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The research method used in this research is descriptive and associative methods. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that income smoothing and firm size have a positive and significant effect on company performance, while financial leverage has a negative and insignificant effect on company performance. Keywords: Income Smoothing, Firm Size, Financial Leverage, Company Performance